Use special Erwa to determine the number of live bacteria in different models - Baghdad Science Journal (مجلة بغداد للعلوم)
Used in the study especially calibrated Erwa to determine the number of neighborhood or the Alayoshi number of bacteria in the count modeling and casting method dishes in addition to using the drop method yielded significant results for a match between the methods used ..